Boron-Insertion-Induced Lattice Engineering of Rh Nanocrystals Toward Enhanced Electrocatalytic Conversion of Nitric Oxide to Ammonia - Han, Peng; Xu, Xiangou; Chen, Weiwei; Zheng, Long; Ma, Chen; Wang, Gang; Xu, Lei; Gu, Ping; Wang, Wenbin; He, Qiyuan; Zeng, Zhiyuan; Wang, Jinlan; et al. (Nano-Micro Letters, 2025)
Electrocatalytic nitric oxide (NO) reduction reaction (NORR) is a promising and sustainable process that can simultaneously realize green ammonia (NH3) synthesis and hazardous NO removal. However, current NORR performances are far from practical needs due to the lack of efficient electrocatalysts. Engineering the lattice of metal-based nanomaterials via phase control has emerged as an effective strategy to modulate their intrinsic electrocatalytic properties. Herein, we realize boron (B)-insertion-induced phase regulation of rhodium (Rh) nanocrystals to obtain amorphous Rh4B nanoparticles (NPs) and hexagonal close-packed (hcp) RhB NPs through a facile wet-chemical method. A high Faradaic efficiency (92.1 ± 1.2%) and NH3 yield rate (629.5 ± 11.0 µmol h−1 cm−2) are achieved over hcp RhB NPs, far superior to those of most reported NORR nanocatalysts. In situ spectro-electrochemical analysis and density functional theory simulations reveal that the excellent electrocatalytic performances of hcp RhB NPs are attributed to the upshift of d-band center, enhanced NO adsorption/activation profile, and greatly reduced energy barrier of the rate-determining step. A demonstrative Zn–NO battery is assembled using hcp RhB NPs as the cathode and delivers a peak power density of 4.33 mW cm−2, realizing simultaneous NO removal, NH3 synthesis, and electricity output. Highlights: 1 Phase regulation of B-inserted rhodium (Rh) nanocrystals is achieved using a facile wet-chemical approach. 2 The B-inserted Rh nanocatalysts exhibit phase-dependent behaviors in electrocatalytic nitric oxide (NO) reduction reaction. 3 The hexagonal close-packed RhB nanocatalysts demonstrate superior electrocatalytic activity in NH3 production with a maximum NH3 yield rate of 629.5 µmol h−1 cm−2 and FENH3 of 92.1%. 4 Theoretical simulations reveal possible origin of the excellent electrocatalytic activity, which could be attributed to the d-band center upshift, enhanced NO adsorption/activation, and reduced energy barrier of rate-determining step.